ANALISIS SWOT, BISNIS MODEL KANVAS, DAN KELAYAKAN KEUANGAN STUDI KASUS BISNIS AMIGURUMI Mâs CROCHET - Hermawan, Fransisca; Salamin, Petrus Pius; Meiliana, Meiliana (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
Amigurumi Ms Crochets business is a craft category in the creative industry. Strength Ms Crochet is divided into 3 competencies, core competencies, and resources, while threats emerge from old competitors and products are easy to replicate. The value offered Ms Crochet is to sell quality amigurumi, timely delivery and products can be tailored to the wishes of consumers. The target market of Ms Crochet is upper middle class society, aged 3+ years, and has an artistic soul. To maintain customer relationships, Ms Crochet uses social media (Line, Instagram, Tokopedia, Website, and Email) for product promotion. Mâs Crochet sales growth increaset 3.1 percent per year assumed to be equal to the growth of the creative industri. Based on the financial feasibility calculation, the NPV earned amounted to Rp4.113.019.207.00 indicating that Mâs Crochet business is feasible to run. Payback period of initial investment for 3.5 months.